Puberty and Influencing Factors in Schoolgirls Living in Istanbul: End of the Secular Trend? - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (AMER ACAD PEDIATRICS, 2011)
OBJECTIVE: To (1) establish the median ages at menarche and pubertal stages and investigate influential factors and (2) assess the secular trend in reaching puberty in a transitional society. MATERIALS AND METHODS: A probit method was used to calculate the median age at menarche and pubertal stages from a cross-sectional study of 4868 healthy schoolgirls (aged 6-18 years) in Istanbul, Turkey. The findings were compared with those from a similar study performed 4 decades earlier. Logistic regression was used to analyze the associations between the odds of attaining puberty stages and putatively influential factors. Simple statistical models were used to test the effects of BMI and consumption of certain foods on the onset of menarche. RESULTS: The median age at menarche is 12.74 years. The median ages at breast stages 2 through 5 are 9.65, 10.10, 11.75, and 14.17 years, respectively, and at pubic-hair stages 2 through 5 are 10.09, 11.19, 12.33, and 14.68 years, respectively. Girls from upper socioeconomic classes are more likely to reach menarche and B4 and B5 stages. Higher BMI seems to be a promoting factor for attaining menarche. Intrauterine growth and gestational age had no effect. The average age at menarche was not associated with the consumption of milk, eggs, chicken, or fish. CONCLUSIONS: The secular trend in puberty is probably about to end in Turkey. Although the median ages at the breast stages show a decreasing trend, the median age at menarche is approximately the same as it was 4 decades ago. Socioeconomic status and BMI are important, and related, factors that affect the age at menarche and pubertal stages. Pediatrics 2011;128:e40-e45
Keywords: BMI; secular trends; socioeconomic status; food intake; SEXUAL-MATURATION; AGE; MENARCHE; GIRLS; PATTERN